2004
DOI: 10.1203/01.pdr.0000125260.46861.32
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Novel Cadherin in the Mouse and Human Intestine

Abstract: Members of the cadherin superfamily mediate critical interactions in tissue differentiation and organogenesis, including differentiation and maintenance of the intestine. In this study, we report the identification and expression of a novel cadherin in the intestinal epithelium. We identified this cDNA by subtraction hybridization and obtained subsequent clones by screening a human cDNA library. Tissue distribution of the mRNA encoding the cadherin was assessed by RNA blot, reverse transcriptase PCR, and in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Conversely, further investigation allowed us to identify μ‐protocadherin as the protein that was primarily responsible for this effect. This protein had been previously isolated by two distinct research groups and, based on its structural properties, assigned to the cadherin protein superfamily 24, 25 . Experimental work developed by these authors allowed them to demonstrate that μ‐protocadherin is prevalently expressed in a number of epithelial tissues, including intestinal mucosa, where it promotes cell adhesion processes such as those responsible for homophilic cell‐cell interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, further investigation allowed us to identify μ‐protocadherin as the protein that was primarily responsible for this effect. This protein had been previously isolated by two distinct research groups and, based on its structural properties, assigned to the cadherin protein superfamily 24, 25 . Experimental work developed by these authors allowed them to demonstrate that μ‐protocadherin is prevalently expressed in a number of epithelial tissues, including intestinal mucosa, where it promotes cell adhesion processes such as those responsible for homophilic cell‐cell interactions.…”
Section: Discussionmentioning
confidence: 99%
“…This protein had been previously isolated by two distinct research groups and, based on its structural properties, assigned to the cadherin protein superfamily. 24,25 Experimental work developed by these authors allowed them to demonstrate that l-protocadherin is prevalently expressed in a number of epithelial tissues, including intestinal mucosa, where it promotes cell adhesion processes such as those responsible for homophilic cell-cell interactions. Taken together, these observations suggested an involvement of l-protocadherin in the biological functions that are normally regulated by other cadherins such as proliferation, apoptosis and development.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, four cadherins were described: epithelial (E-), neural (N-), placental (P-) cadherins and L-CAM [ 32 ]. Although the intestine expresses several members of the cadherin family, E-cadherin is the predominant cell adhesion molecule in the intestinal epithelium [ 33 ]. In our study, the expression of E-cadherin (pictures not shown) in the brush border of villi was not modified after FMSpH6 administration, which would indicate that the active components of the FMSpH6 act at different and specific levels, thus underlying the importance of the knowledge not only of the active constituents responsible for each effect but also of the target sites.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report has identified a novel member of the cadherin protein superfamily that has been named μ-protocadherin [14,15]. Experimental work developed by these authors allowed them to demonstrate that μ-protocadherin is expressed in a number of epithelial tissues, including intestinal mucosa, where it promotes homophilic cell-cell contacts, suggesting an evident functional similarity with E-cadherin.…”
Section: Introductionmentioning
confidence: 99%